Using Communicative Language Teaching Method in Teaching English to Senior High School Students in Karo Regency - T. Thyrhaya Zein; Rudy Sofyan; T. Silvana Sinar; Rusdi Noor Rosa; Bahagia Tarigan (LingPoet: Journal of Linguistics and Literary Research, 2026)
One persistent challenge in English language teaching (ELT) at senior high schools in Karo Regency, Indonesia, is teachers’ limited access to and familiarity with communicative teaching methods. Professional training that provides teachers with communicative methodologies constitutes a viable strategy to tackle this challenge. This study aims to examine the advantages of implementing Communicative Language Teaching (CLT) in English instruction at the senior high school level in Karo Regency. Using a descriptive research design, the study involved English teachers who had previously received training in the CLT method. Data were collected through classroom observations and semi-structured interviews and analyzed descriptively. The findings reveal five major advantages of CLT implementation: (1) increased classroom interaction, (2) reduced student boredom, (3) decreased speaking-related shyness, (4) a more enjoyable and engaging learning atmosphere, and (5) improved speaking fluency. These results indicate that CLT effectively supports teachers in achieving the primary objective of ELT, namely the development of students’ communicative competence. The research points out the need for continuous professional development in communicative methodologies to enhance the quality of English language instruction in regional educational contexts.